PENGEMBANGAN VIRTUAL LAB AI-STEM UNTUK MENINGKATKAN LITERASI SAINS DAN KREATIVITAS SISWA PADA PEMBELAJARAN BIOLOGI DI DAERAH KABUPATEN PULAU TALIABU - Ihsan, Ikhlashul; Vianti, Eva; Apling, Mujais (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Scientific literacy and creativity are essential competencies in biology learning, yet previous evidence from Taliabu Island indicates that both remain at moderate levels and are strongly shaped by external learning conditions. This study developed an AI-STEM Virtual Lab adapted to the characteristics of an island region and examined its feasibility and effectiveness. The study combined product development, expert validation, and a quasi-experimental nonequivalent control-group design involving 62 students (31 experimental; 31 control). Scientific literacy and creativity were measured using 15-item four-point Likert instruments, while media feasibility was assessed by two experts using 48 indicators. The corrected expert-validation score was 88.75%, indicating very high feasibility with minor revisions. Reliability coefficients ranged from 0.805 to 0.906. Wilcoxon tests showed significant pretest-posttest improvement in all groups (p < .001). Scientific literacy in the experimental group increased from 50.54 to 69.03 (N-gain = 0.378), whereas the control group increased from 41.67 to 61.56 (N-gain = 0.321); however, the between-group N-gain difference was not significant (p = .176) and baseline literacy differed significantly. Creativity showed a clearer intervention pattern: baseline scores were equivalent (p = .848), while experimental N-gain (0.313) exceeded control N-gain (0.201; p = .049). The findings indicate that the AI-STEM Virtual Lab is highly feasible and promising, particularly for strengthening student creativity, while claims regarding superior scientific-literacy gains require further multi-school testing with better baseline equivalence.